ADAPTING INTERACTIVE NEWS PROGRAM OF SUARA ANDA TO TEACH SPEAKING AT SENIOR HIGH SCHOOL - Albeni Yostija; Havid Ardi (Universitas Negeri Padang, 2013)
AbstractThis article discusses the use of techniques of adapting an interactive news program of